2006
DOI: 10.1021/jf051979g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methyl Jasmonate on Secondary Metabolites of Sweet Basil (Ocimum basilicumL.)

Abstract: The effect of methyl jasmonate (MeJA) in terms of its induction of inherent bioactive chemicals in sweet basil (Ocimum basilicum L.) was evaluated after MeJA was sprayed on healthy basil plants. The total phenolic content of the sweet basil significantly increased after 0.1 and 0.5 mM MeJA treatments compared with the control not subjected to MeJA. Two phenolic compounds, rosmarinic acid (RA) and caffeic acid (CA), were identified as strong antioxidant constituents of the sweet basil. Their amounts also signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
114
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(136 citation statements)
references
References 44 publications
(47 reference statements)
17
114
2
1
Order By: Relevance
“…Similar trend of results was reported by Phatak and Heble (2002), Kim et al (2006), Namdeo et al (2007) and Roy and Mukhopadhyay (2012).…”
Section: Resultssupporting
confidence: 89%
“…Similar trend of results was reported by Phatak and Heble (2002), Kim et al (2006), Namdeo et al (2007) and Roy and Mukhopadhyay (2012).…”
Section: Resultssupporting
confidence: 89%
“…Loivamäki et al (2004) also reported that jasmonate induction led to an increase in tobacco alkaloids, phenolics, and diterpene glycosides in Nicotiana attenuate. Moreover, the impacts of MeJA on the biosynthesis of volatile compounds in climacteric and non-climacteric fruits, such as apples and strawberries, respectively, have also been reported (Ayala-Zavala et al, 2005;Kim et al, 2006;de la Peña Moreno et al, 2010a;2010b;Belhadj et al, 2008;Gohain et al, 2012). However, investigations toward the effects of exogenous MeJA on tea aroma have been scarcely reported.…”
Section: Introductionmentioning
confidence: 99%
“…To elicit abundant flavonoid accumulation in plant-cell cultures MJ has been often used (Fang et al 1999). Total phenolic compounds content increased after MJ treatments of romaine lettuce (Lactuca sativa L.) and sweet basil (Ocimum basilicum L.) (Kim et al 2006;Kim et al 2007). Authors of these studies explain higher accumulation of phenolics due to induction by MJ of phenylalanine ammonia-lyase (PAL) activity.…”
Section: Introductionmentioning
confidence: 99%